The Effect of Governance Quality on Economic Growth in Asean Countries - Fattan Raja Mulya Darajat; Suhal Kusairi (Cakrawala Repositori IMWI)
Economic growth in ASEAN countries exhibited fluctuating and uneven trends during the last decade, reflecting differences in governance quality among member states. This study aims to examine the influence of Voice and Accountability, Political Stability, Government Effectiveness, Regulatory Quality, Rule of Law, and Control of Corruption on economic growth in ASEAN countries. A quantitative approach was employed using panel data from 10 ASEAN countries during 2014-2024, analyzed using panel data regression. The findings reveal that Political Stability (PS) and Control of Corruption (CC) exhibit statistically significant effects on economic growth at the 5% and 10% significance levels, whereas the remaining governance indicators are statistically insignificant. The study concludes that political stability is a key institutional prerequisite for sustaining economic growth in ASEAN countries.